Ultraviolet-Induced Fluorescence Dermoscopy, a Novel Diagnostic Technique in Dermatological Practice: A Systematic Review - Yasmeen Jabeen Bhat; Mohd Shurjeel Ul Islam; Enzo Errichetti (Indian Dermatology Online Journal)
Introduction: Ultraviolet-induced fluorescence dermoscopy (UVF dermoscopy) is a novel diagnostic technique for identifying and diagnosing numerous skin tumors, inflammatory dermatoses, and infectious diseases. The ultraviolet (UV) band has a wavelength ranging from 10 to 400 nm. When intense UV radiation with shorter wavelengths strikes a target chromophore, visible light (VL) with a longer wavelength and lower energy is produced in the skin. This VL is apparent to the naked eye and is referred to as fluorescence. Aim: The current review compares ultraviolet fluorescence dermoscopy (UVFD) and polarized dermoscopy (PD) features in various dermatological disorders. Materials and Methods: This review was performed in accordance with PRISMA (Preferred Reporting Items for Systematic Reviews and Metanalyses) guidelines. A comprehensive search of the literature was carried out through the PubMed and Google Scholar electronic databases from inception to 25th December 2023 using the following search terms: “UV dermoscopy” OR “ultraviolet fluorescence dermoscopy” OR “ultraviolet-induced fluorescence dermoscopy” OR “Ultraviolet-induced fluorescent dermoscopy”. Titles, abstracts, and full texts were screened by two independent reviewers to select papers dealing with UVF-dermoscopy. Results: A total of 23 relevant articles were included in this systematic review, including a total of 313 patients. Pigmented skin tumors included 209 patients, Fordyce spot mimickers (13), scabies (57), biopsy site (20), psoriasis (3), corynebacterium infections (2), fungal infections (4), vitiligo (3), acne folliculitis (1) and glomus tumors (1). Levels of evidence (LoE) was 3 and 4 in only two included studies; the rest had a LoE of 5. Discussion: UVF dermoscopy is a new diagnostic and prognostic tool for neoplastic and non-neoplastic dermatological conditions. This is the first systematic review of its sort that compares and categorizes dermoscopic findings in UVF and polarized light in dermatological practice. As UVFD does not penetrate deeper skin layers, we observed that it is a better way to distinguish features restricted to the skin’s superficial layers in neoplastic diseases. As a result, tumor-free margins and improved surgical outcomes can be achieved. More favorable outcomes for evaluation and treatment were seen with non-neoplastic conditions. Limitations included a lack of studies with a high level of evidence, control groups, and larger sample sizes. Conclusion: We concluded that UVFD will improve clinical diagnosis, disease management, and outcomes. More clinical trials with larger sample sizes are recommended to better understand this novel and intriguing new diagnostic tool.